2022
DOI: 10.4314/ijbcs.v16i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Etude ethnopharmacologique des plantes utilisées dans la préparation des phytomédicaments extemporanés à Tomety-Kondji, canton riverain au Parc National de Togodo-Sud du Togo

Abstract: Le canton de Tomety-Kondji riverain au Parc National de Togodo-Sud (PNTS) (préfecture de Yoto au Togo) est constitué de villages aux potentiels énormes en médecine traditionnelle. La présente étude a été entreprise pour recenser les plantes et recettes de plantes des préparations extemporanées de phytomédicaments (PEP) (décocté et macérât) utilisées dans les soins de santé primaire de la population en vue de leur valorisation. L’interview semi-structurée a été la méthode de collecte des données à l’aide d’un q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The interest in leaves can be explained by the fact that they are the storage site for secondary metabolites, which are responsible for the plant's biological properties (Nesrine et al, 2022). However, studies carried out by Ouro-djeri et al, (2022) and Ouadeh et al, (2021) showed that leaves were the most frequently used drugs in the preparation of traditional medicinal recipes, with %s of 53.59% and 22%, respectively, which is confirmed by the results of our survey. Finally, Mawunu et al, (2022) report that J. curcas leaves are used to treat teigns, dermal infection and stomach ache in the small town of Songo in northern Angola.…”
Section: Hierarchical Ascendant Classificationsupporting
confidence: 84%
See 1 more Smart Citation
“…The interest in leaves can be explained by the fact that they are the storage site for secondary metabolites, which are responsible for the plant's biological properties (Nesrine et al, 2022). However, studies carried out by Ouro-djeri et al, (2022) and Ouadeh et al, (2021) showed that leaves were the most frequently used drugs in the preparation of traditional medicinal recipes, with %s of 53.59% and 22%, respectively, which is confirmed by the results of our survey. Finally, Mawunu et al, (2022) report that J. curcas leaves are used to treat teigns, dermal infection and stomach ache in the small town of Songo in northern Angola.…”
Section: Hierarchical Ascendant Classificationsupporting
confidence: 84%
“…Older people were more likely than younger people to know how to use J. curcas. These results corroborate those ofOuro-djeri et al, (2022), andNesrine et al, (2022), who showed that older people were the most likely to have access to knowledge about traditional medicine. This is probably the main reason why this profession is practised by older people.…”
supporting
confidence: 89%
“…The code of ethics of the international society of Ethnobiology was respected during the interview. A total of 11 dissertations papers [6,[36][37][38][39][40][41][42][43][44][45] were retained. The keywords medicinal plant AND TOGO, plant extract AND TOGO, medicinal*, medicinal plant* had been used.…”
Section: Data Collectionmentioning
confidence: 99%